Rapid evaluation of platelet function using the Multiplate® Analyzer. (December 2014) - Würtz, Morten; Hvas, Anne-Mette; Christensen, Kristian Hylleberg; Rubak, Peter; Kristensen, Steen Dalby; Grove, Erik Lerkevang
Abstract Rapid evaluation of platelet function may be advantageous in the setting of surgical and interventional procedures to tailor treatment of ongoing bleeding. We investigated if platelet function testing performed with the Multiplate® Analyzer (Roche Diagnostics, Mannheim, Germany) only 5 minutes after blood sampling yields reliable test results compared to analyses performed 30 minutes after sampling as currently recommended. We included 48 patients with type II diabetes and stable coronary artery disease treated with aspirin 75 mg daily and 50 healthy individuals not taking any medications. Platelet aggregometry by the Multiplate® Analyzer was performed 5 and 30 minutes after blood sampling using arachidonic acid (1.0 mM), collagen (3.2 µg/ml) and adenosine diphosphate (ADP; 6.5 µM) as agonists. Compliance with aspirin was verified by serum thromboxane B2 measurements. Aggregation levels assessed 5 minutes after blood sampling correlated strongly with those assessed after 30 minutes irrespective of the agonist used (r-values 0.75–0.89, p values <0.0001). Aggregation levels were 4–8% lower and displayed a larger standard deviation when measured 5 minutes after sampling, compared to 30 minutes after sampling. Weak, but significant correlations were observed between platelet aggregation and platelet count (r-values = 0.28–0.39; p values <0.01). The currently recommended 30-minute standing time can be omitted, when platelet aggregation is measured using the Multiplate® Analyzer. Platelet aggregation measured 5 minutes after blood sampling correlates strongly with aggregation measured 30 minutes after sampling, but yields slightly lower aggregation levels. The Multiplate® Analyzer enables rapid on-site evaluation of platelet function.